Visionary Leadership and Organizational Culture on Teacher’s Performance - Kurniadi, Roni; Lian, Bukman; Wahidy, Achmad (Journal of Social Work and Science Education, 2020)
This study determined the effect of Visionary Leadership and orgazitional culture on the performance of Vocational High School Teacher in Prabumulih City. This research uses quentitative approach with Survey Method. This study population of 125 people, namely vocational High School teacher in Prabumulih city. The research sample of 30 people. The sampling technique in this study is random sampling. Data collectional technique using documentational and questionnaire. Data were analyzed using simple regression techniques and Multiple regression techniques. The result showed that: (1) visionary leadership had a positive and significant effect on the performance of Vocational High Shcool Teachers in Prabumulih City; (2) organization culture had a positive and significant effect on the performance of Vocational High Shcool Teachers in Prabumulih City, and (3) visionary leadership and Organization culture jointly have a positive and significant effect on the performance of Vocational High Shcool Teachers in Prabumulih City.